Attending to the voices of parents of children with Reactive Attachment Disorder - Schlein, Candace; Taft, Raol J. (Frontiers in Education, 2023)
This article discusses the findings of a narrative inquiry case study into the school experiences of adoptive and/or foster parents with children with Reactive Attachment Disorder. The data from families of children with an attachment disorder were collected through interviews and support group observations. The major finding of this study is that the caregivers of students with this attachment disorder feel as though they have been silenced by schools. The data highlights how the social, emotional, and academic needs of children with attachment disorders might not align with the components of educational accountability that are currently in place. Considerations are also raised about how educational accountability for students with special needs might need to be re-imagined in accordance with the perspectives and experiences of parents on school landscapes.